The Strategies for Addressing Main Characters in Isan Literature: A Case Study of Khulu-Nang Ua - Itsarate Dolphen (Journal of Management Practices, Humanities and Social Sciences, 2020)
This paper aims at exploring the strategies for addressing main characters in the Northeastern Thai literature of Khulu-Nang Ua. Khulu-Nang Ua is one of the most famous Isan literature in Northeast Thailand. This literature belongs to a tradition of tragic romances as Romeo and Juliet but in Isan version. The plot is based on an Isan folktale written in verse without any evidence of the writer but revised by Preecha Phinthong. Besides having good plot and using beautiful words to compose this tragic story, the strategies the writer used to address the main characters, Khulu and Nang Ua, are remarkable. Only the main characters, Khula (the hero) and Nang Ua (the heroine) are explored. This paper used quantitative methodology by undertaking a content analysis to collect data from the the Northeastern Thai literature. The findings reveal that there are two main strategies for addressing main characters in Khula-Nang Ua which are 1) direct address and 2) indirect address. For the direct address, there are four sub-strategies to be used as follows: 1) name, 2) name title + name, 3) name title + name + modifier, and 4) name + modifier. As for the indirect address, there are four sub strategies as well that the writer used them to address main characters in this story as follows: 1) metaphorical words, 2) pronouns, 3) name title, and 4) name title + modifier. It was found that the metaphorical words was often used as the main strategies to address the characters, especially for Nang Ua. This is because many metaphorical words were found and used diversely.